Learning and teaching using digital books : opportunities and constraints - Gonçalves, Daniela (2016)
It is increasingly noticeable that society is constantly evolving in a complex way and school life reflects this strong influence. Therefore education also becomes a very complex and everchanging organization. This social scenario urges us to focus on the quality of education, placing the teacher at its core and on the quality of the pedagogical intervention. This leads us to some questions: Do teachers reflect on their teaching? Do teachers question the way they teach? Do teachers justify the use of the teaching materials they select? What about the methods they use? Do they identify the results of their teaching? Taking into account the teaching strategies that they use and the learning process, do teachers question those results and how to improve? With these concerns, it is essential to link the use of strategies that assume the effective and enriching development of theoretical and practical interaction processes to the learning andteaching using digital books: opportunities and constraints. It is in this context that we will present the main results of a qualitative research held in a public school. Twelve teachers of the first cycle of basic education have participated in this study.